Evaluación semicuantitativa de glucógeno megacariocítico para el diagnóstico de púrpura trombocitopénica idiopática - Parreño T, Juan M (2009)
The aim of this study was to determine semiquantitatively megakaryocyte glycogen and related parameters as an aid to diagnosis and treatment of idiopathic thrombocytopenic purpura (ITP). The tests were applied to 100 patients diagnosed with ITP from various hospitals and clinics, and 100 apparently healthy subjects who was gave informed consent according to the Declaration of Helsinki. Investigating the presence of glycogen in megakaryocytes of bone marrow smears using the method of peryodic acid-Schiff and complementary tests of hemostasis: platelets by the method of Rees-Ecker, mean platelet volume (MPV) using the automatic analyzer Sysmex XE-2100, prothrombin time, partial thromboplastin time (PTT), bleeding time, fibrinogen, hemoglobin and red blood cell count by the usual methods. We conclude that patients with ITP megakaryocyte glycogen had decreased (100%), alterations in some coagulation parameters such as increased bleeding time (98%), decreased number of platelets (100%) remaining prothrombin time, PTT and fibrinogen, and increased MPV (88%). In addition, we found a significant positive correlation between decreased levels of platelets and the MPV.